2014
DOI: 10.1093/humrep/deu318
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances in a community-based sample of women with polycystic ovary syndrome

Abstract: Our results indicate that assessment and management of both sleep and mental health problems in women with PCOS should be undertaken. Longitudinal data would be valuable to see how poor sleep affects longer-term health profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
64
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 38 publications
3
64
2
5
Order By: Relevance
“…Recent findings suggest that there are circadian rhythm and sleep disturbances in women with diagnosed PCOS [20, 21]. We also observed that women with less than 6 hours of sleep had a 1.7-fold increased risk of having long menstrual cycles (more than 35 days) typical of PCOS, although this association did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 50%
“…Recent findings suggest that there are circadian rhythm and sleep disturbances in women with diagnosed PCOS [20, 21]. We also observed that women with less than 6 hours of sleep had a 1.7-fold increased risk of having long menstrual cycles (more than 35 days) typical of PCOS, although this association did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 50%
“…Similar proportion of women complained of difficulty falling asleep in study and control group was observed, however more than two fifth of PCOS patients reported unintended early awakening, whereas it was observed only in a few percent of healthy women. The phenomenon was related to Moran et al (2015), but there are some other available data that indicate comorbidity of depressive and anxiety disorders with sleep disorders in women with PCOS [8]. Sleep disorders, as it occurs, might be the one of predictors of depression in women suffering from PCOS [24].…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disturbances in patients suffering from PCOS are described in adult women, but they can be also observed even in adolescent patients [22]. Moran et al (2015) have tried to reveal, that other forms of sleep disorders than OSA are also common in women suffering from PCOS. For this purpose they made investigation of sleep disturbances in a community-based sample of women with and without PCOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increased risk was present in only obese women with PCOS, indicating that BMI was the only independent predictor of OSA risk on Berlin Questionnaire (23). Another study, investigating sleep disturbances using a modified version of Jenkins Sleep Questionnaire in a community-based sample of women with and without PCOS, showed that sleep disturbances were almost twice as common in women with PCOS compared with women of similar age without PCOS and difficulty achieving and maintaining sleep were most problematic (24). Findings about sleep architecture in adults with PCOS are conflicting.…”
Section: Discussionmentioning
confidence: 99%